PENGELOLAAN SUMBERDAYA HAYATI BAGI PEMENUHAN KEBUTUHAN PANGAN DAN GIZI - Mustafril .; Budi Indra Setiawan; M. Yanuar J. Purwanto; Lilik B. Prasetyo; Drajat Martianto (Jurnal Keteknikan Pertanian, 2006)
Abstract Requirement of food and nutrients in a specified is a determined by the growth of population, avai1ability of agriculture, plantation, animl husbandry and fisheries resources. Sufficient food forconsumption can be calculated bused on sexes, ages and other human conditions. To fulfill food sufficency is also dependent upon non-consumptive use of the resources such as for seed,feed, industry and export. Comsumption of both food and nutrients in Indonesia follows the Recommended Dietary Allowance (RDA) with the approach on the Desirable Dietary Pattern (DDP). Goals of and management based on its sustability are necessarily oriented to produce agricultural commodities to meet the requirement of nutrients and food in a balanced condition. Thus, It Is of Interest to optimize bio-resource management with respects to the fulfillment of food and nutrient sufficiency in a localized area. The use of linear programming may give possible by the people living there. This peper Introduces an approach on bio-resouce management with the main concern  is to produce diversified foods sustainably. Keyword.: food, nutrients, bio-resource management, linier programming